Strategic Position and Trade Union Power: A Comparative Study of the Automotive, Chemical-Petrochemical and Oil Sectors in Argentina, 2003-2015 - Marticorena, Clara (2022)
The aim of this paper is to analyse empirically the importance of union strategies as a moderatingvariable between unions’ structural and associational power and their bargaining and mobilisationpower. To this end, we selected three unions, one from each of three strategic industrial sectors inthe Argentinian national economy – automotive, chemical and edible oils – and analysed theirdynamics of collective bargaining and labour conflict in the 2003–2015 period. The research isbased on a review of secondary sources (collective bargaining agreements and conflict databases)as well as primary sources (semi-structured interviews with managers, trade union leaders, workerrepresentatives and activists). Whereas workers in each of these sectors have a similarly high degreeof structural power, we observed differences among the sectors in working, wage andorganisational conditions. These differences are associated with three different union strategies forbuilding union power, which we identify as partnership, confrontational and combative.